Downregulation of METTL14 increases apoptosis and autophagy induced by cisplatin in pancreatic cancer cells. (May 2020) - Kong, Fanhua; Liu, Xi; Zhou, Yan; Hou, Xuyang; He, Jun; Li, Qinglong; Miao, Xiongying; Yang, Leping
Abstract: Pancreatic cancer is a leading cause of cancer-related death worldwide. Cisplatin is an essential drug treating patients with BRCA1/2 or PALB2 mutations. Whether other genetic determinants of cisplatin sensitivity exist and their underlying mechanisms remain unclear. Immunohistochemistry was used to determine METTL14 expression in pancreatic cancer tissues and non-tumoural tissues. Cell proliferation was detected with CCK-8 assays. Apoptosis was analysed via Western blotting and flow cytometry, and autophagy was analysed via Western blotting and immunofluorescence. In this work, we found higher METTL14 expression in pancreatic cancer tissues than in non-tumoural tissues, and METTL14 expression was associated with pathological characteristics. Downregulation of METTL14 with siRNA sensitized pancreatic cancer cells to cisplatin. Specifically, apoptosis and autophagy were significantly enhanced in METT14 knockdown cells compared with control cells after treatment with cisplatin. Mechanistically, the AMPKα, ERK1/2 and mTOR signalling pathways were disturbed by downregulation of METTL14. We further found that METTL14 knockdown-mediated autophagy was dependent on mTOR signalling and that mTOR activation decreased autophagy to the level observed in the control group. Collectively, our results indicate that METTL14 is upregulated in pancreatic cancer, downregulation of METTL14 sensitizes pancreatic cancer cells to cisplatin by enhancing apoptosis, and autophagy is improved via an mTOR signalling-dependent pathway.